2014
DOI: 10.1007/s00428-014-1627-1
|View full text |Cite
|
Sign up to set email alerts
|

The combination of CD99 and NKX2.2, a transcriptional target of EWSR1-FLI1, is highly specific for the diagnosis of Ewing sarcoma

Abstract: Ewing sarcoma (ES) is a high-grade malignant neoplasm primarily affecting children and young adults. The diagnosis of ES is often difficult because of its broad differential diagnosis comprising a diverse group of small round cell tumors (SRCTs). Although the identification of tumor type-specific fusion genes by molecular testing is the gold standard for the diagnosis of ES, such approaches are not always available in a routine pathology practice. Thus, a reliable immunohistochemical marker is required. A rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 41 publications
3
58
0
Order By: Relevance
“…Since its identification in gene expression studies, 10 NKX2-2 has been described as a diagnostic immunohistochemical marker for Ewing sarcoma, 11 in a similar manner as DOG1 (ANO1) for gastrointestinal stromal tumor, 20 TLE1 for synovial sarcoma, 21 and MUC4 for low-grade fibromyxoid sarcoma. 22 Two prior studies demonstrated NKX2-2 positivity in 80-93% of Ewing sarcomas; 11,12 however, only cases with classic morphology and EWSR1-FLI1 rearrangements were evaluated. In this study, we examined 40 genetically confirmed Ewing sarcomas, including 4 with atypical large-cell cytomorphology, 4 from uncommon locations (cutaneous and uterine), and 3 with confirmed EWSR1-ERG rearrangements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since its identification in gene expression studies, 10 NKX2-2 has been described as a diagnostic immunohistochemical marker for Ewing sarcoma, 11 in a similar manner as DOG1 (ANO1) for gastrointestinal stromal tumor, 20 TLE1 for synovial sarcoma, 21 and MUC4 for low-grade fibromyxoid sarcoma. 22 Two prior studies demonstrated NKX2-2 positivity in 80-93% of Ewing sarcomas; 11,12 however, only cases with classic morphology and EWSR1-FLI1 rearrangements were evaluated. In this study, we examined 40 genetically confirmed Ewing sarcomas, including 4 with atypical large-cell cytomorphology, 4 from uncommon locations (cutaneous and uterine), and 3 with confirmed EWSR1-ERG rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism underlying NKX2-2 expression in mesenchymal chondrosarcomas is unknown. Although a combination of CD99 and NKX2-2 has been suggested to be highly specific for the diagnosis of Ewing sarcoma, 12 this would not exclude mesenchymal chondrosarcomas, which are often positive for both markers.…”
Section: Nkx2-2 In Ewing Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not excluded that sarcoma cells were suppressed by non-tumor cells such as fibroblasts as often observed in long-term cultures. We therefore investigated the morphology and CD99 expression 29 in these cells ( Figure 5). BX-derived cells grew as loosely attached patches that did not reach confluence.…”
Section: Ewing Patientmentioning
confidence: 99%
“…Recently, the immunohistochemical expression of NKX2.2, a putative transcriptional target of EWSR1‐FLI1, was evaluated on 46 ES and 85 non‐ES SRCT. They demonstrated a 98% specificity of NKX2.2 when combined with CD99 . Thus, it seems to be a powerful diagnostic tool that can differentiate ES from other SRCT, avoiding molecular analysis, which is costly, laborious, and only available at a limited number of large centers.…”
Section: Introductionmentioning
confidence: 99%